The Impacts of Customer Focus on Innovation in Service Organizations - Bon, A.T.; Mustafa, E.M.A. (Journal of Engineering and Technology (JET), 2014)
This paper investigates the impact of customer focus on process innovation and administrative innovation in service organizations. The data were collected from service organizations in Malaysia. The organizations are from different service subsectors and different sizes. Confirmatory Factors Analysis (CFA) was used to confirm and validate the constructs included in the proposed theoretical model. Structural Equation Modeling (SEM) was used to test the hypotheses. Results of hypothesis testing revealed that customer focus has a positive impact on both process and administrative innovations in the surveyed organizations. This study added the perspective of service organizations to the debate about the relationship between customer focus and innovation. The findings of this study will help managers to positively linking customer focus practices with process and administrative innovation.